A 76-Year-Old Woman Returning From Venezuela With Unusual Eruptions on the Feet - Kosumi, Hideyuki; Iwata, Hiroaki; Miyazawa, Hajime; Tsujiwaki, Masumi; Mai, Yosuke; Ando, Satomi; Ito, Takuya; Yamano, Kimiaki; Shimizu, Hiroshi (Clinical infectious diseases, 2018)
This is a typical case of tungiasis, a parasitic disease caused by the sand flea Tunga penetrans. The flea favors warm, dry environments, and tungiasis is prevalent in rural Central and South America, the Caribbean and sub-Saharan Africa. The gravid female sand flea penetrates mammalian skin headfirst, burrowing her mouthparts into the superficial dermis to feed on the host’s blood. As its abdomen swells, the pregnant flea becomes spherical and forms unique, uniform eruptions.